FAKTOR YANG MEMPENGARUHI PERILAKU WANITA DALAM MELAKUKAN DETEKSI DINI METODE PAP SMEAR DI PUSKESMAS PAMOLOKAN KABUPATEN SUMENEP - Dian Permatasari (Wiraraja Medika : Jurnal Kesehatan, 2015)
mortality rates are high. Currently the world is estimated to be more than 493.243inhabitants with mortality due to these cancers as much as 273.505 inhabitants per year. InIndonesia there are 15,000 new cases per year, with a mortality rate of 7,500 per year. Papsmear examination is one way to detect cervical cancer cervical cancer treatments so thatcan be done before spreading to the outside of the uterus.The purpose of this research is to know some of the factors that affect the behavior ofwomen in the early detection of cervical cancer pap smear method at the Gatot SoebrotoDESCRIPTION Jakarta by 2013. This research is explanatory research with cross sectionalapproach. The technique of sampling with consecutive sampling.The results of this research indicate 68.8% have a pap smear that risky behavior ismade up 53.2% do not regularly perform pap smear and 15.6% did not perform a pap smear.The analysis of the test using the bivariat chi square shows there are significant variablesaffecting 8 behavior of women in the early detection of cervical cancer pap smear method,i.e. the employment history, age of first sexual intercourse, parity, wife KB, knowledge aboutcervical cancer, knowledge about early detection method of pap smear, attitude towardscervical cancer, attitudes towards early detection method of pap smear, pap smear servicesaccess and support family. Logistic regression test results obtained, the dominant variablesaffect the behavior of women in the early detection of cervical cancer pap smear method, i.e.,knowledge about cervical cancer, knowledge about early detection method of pap smear,attitude towards cervical cancer. Of research results it is recommended to all partiesconcerned to enhance the efforts of cervical cancer through the handling of cross-cuttingterkoordinir KIE to the community in General, especially to the women and the elderly to payattention to the Ministry early detection (pap smears).Keywords : Behaviour, Women, Early Detection, Pap Smear